PENGARUH KEBIJAKAN ALOKASI ASET, PEMILIHAN SAHAM DAN TINGKAT RISIKO TERHADAP KINERJA REKSADANA CAMPURAN PERIODE 2010-201 - IDA YANTI, NUR (Jurnal Ilmu Manajemen (JIM), 2017)
The research is racing about mutual funds which one of the investment type that many investors demand because it is cosidered as an investment that can minimaze risk. In this study more emphasis on the type of mixed mutual funds due to an increase in NAB/Net Asset Value fluctuating growth. This study aims to determine whether the variables of asset allocation policy, stock sellection,and risk level affect the performance of mutual funds. The population used in this study is the whole product of mixedmutual funds. While for the sample only 7 mutual fund products that meet the criteria by sampling using purposive sampling technique. The data needed in the study of secondary data obtained from Dunia Investasi in the form of NAB/Net Asset Value report. The results of this study indicaate that the variable aset allocation policy has a positive effect on the performance of mutual funds provied the higher the asset alloaction, the higher expected return of investors. Variable stock sellection does not affect the performance of mutual funds proved that the sellection of shares influenced by several factors such as market prices, economic conditions and asset allocation level. The last variable risk level does not affect the performance of mutual funds proved that the higher the risk the lower the performance of mutual funds due to depend on the policy of asset allocation, stock sellection and economic conditons.. Keywords: mixed mutual fund performance, asset allocation policy, stock sellection, level of risk.